Improved Caffarelli-Kohn-Nirenberg and trace inequalities for radial functions - de Napoli, Pablo Luis (2012)
We show that Caffarelli-Kohn-Nirenberg first order interpolation inequalities as well as weighted trace inequalities in Rn × R+ admit a better range of power weights if we restrict ourselves to the space of radially symmetric functions.